Pengembangan LKPD Augmented Reality dengan model Discovery Learning sebagai media pembelajaran interaktif - TRI DESSY DAMAYANTI (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2022)
School digitization, which is currently being intensified by the government, provides an opportunity for teachers to develop creativity and learning innovations that suit the needs of students. Along with the implementation of the 2013 curriculum which aims to challenge the education system in Indonesia so that students have 21st century skills. This indirectly also requires the education system, especially in schools, to be carefully prepared, although the learning process currently applied still tends to focus on teacher. This condition is in stark contrast to the 2013 curriculum education system, where the learning process prioritizes the active participation of students. Starting from these problems, the authors try to provide solutions by developing learning media with Augmented Reality-based multimedia. The learning media that will be developed is modeling of cube nets. This study aims to develop Augmented Reality-based multimedia to support the development of learning media. The research method used in this research is research and development. Data collection techniques were carried out by interviews, questionnaires, and literature studies. Then, the data was then analyzed using qualitative descriptive analysis. The results of this study are the modeling product of cube nets and the results of the analysis of student responses to the product. The results of the questionnaire show the level of attention, relevance, confidence, and satisfaction of 80%, 76%, 75%, and 77%. These results classify for the use of learning media with an average score of 77%. These results are categorized as good for the use of learning media. The development of this media is expected to be the basis for developing Augmented Reality-based learning media designs as interactive learning media.